Analisis Kerentanan Sosial Masyarakat dan Adaptasi Perubahan Iklim di Kampung Gemblakan Atas, Kota Yogyakarta - Putri, Teti Deliany; Sunarsih, Sunarsih; Muhammad, Fuad (Universitas Sebelas Maret, 2019)
Natural disasters because of the climate change have an impact on increasing vulnerability in the community. The location of the study in Gemblakan Atas Village located beside of the Code River, the location makes the condition of the population vulnerable to the danger of flooding and landslides. The purpose of this study was to determine the social vulnerability and adaptation to climate change. Social vulnerability was analyzed by comparing vulnerability on the sub-district scale using the Geographic Information System (GIS) with scoring and weighting methods. Whereas to find out the climate change adaptation in the method used in this study is a qualitative research method. Sources of data used are obtained from primary data, namely through interviews with resource persons. While secondary data comes from document data, archives, and other sources related to research. Social vulnerability represents a condition of the level of social fragility in the face of disasters. Vulnerable social conditions can cause large losses if a disaster occurs. In this study the indicators of social vulnerability used include population density, the dependency ratio of the elderly and toddlers to the productive age, sex ratio and disabled people. Based on the calculation results the highest social vulnerability index value occurred in 5 (five) sub-districts and 10 (ten) other districts with moderate vulnerability index values. So based on this analysis the Gemblakan Atas Village is located in Danurejan District which has the highest level of social vulnerability in Yogyakarta city (IKS Value 0.86). In the face of disasters due to the effects of climate change, several adaptation activities carried out by the people in Gemblakan Atas Village include planting the tree, water conservation, household waste management, and making environmental protection posters.